Cost-effectiveness of State Policies Banning Pregnancy Termination After Down Syndrome Diagnosis [28A]. (May 2017) - Scrivner, Karen; Rodriguez, Maria; Savitsky, Leah; Zwerling, Blake; Bullard, Kimberley; Caughey, Aaron
Abstract : INTRODUCTION: Three states have passed recent laws prohibiting abortion in cases of fetal abnormality, most notably Down syndrome. Data to demonstrate the impact of these restrictions are lacking. Our study sought to evaluate the cost-effectiveness of these policies for pregnancies affected by Down syndrome. METHODS: A decision-analytic model was constructed using TreeAge 2016 software. Probabilities, costs and utilities were derived from the literature. Our primary outcome was cost, and our secondary outcomes included: cost per quality adjusted life year (QALY), procedure-related fetal loss (PRL), births affected by Down syndrome, intrauterine fetal demise (IUFD), and pregnancy termination. The cost-effectiveness threshold was set to 100, 000 per QALY. Sensitivity analysis was performed to determine the robustness of the model. RESULTS: In a theoretical cohort of 159, 936 women representing annual live births in states affected by this ban, this policy results in an additional annual cost of 340 million, which corresponds to 2, 124 per pregnant woman. It also results in a greater number of live births affected by Down syndrome—223 compared to 124 with no policy. The policy would not be expected to change the rates of PRL and IUFD, while 99 fewer abortions would be expected with a decrease of 494 QALYs. CONCLUSION: Although policies restricting abortion in cases of a Down syndrome diagnosis result in fewer pregnancy terminations, they do lead to a greater economic burden. States should keep this in mind along with the ethical implications of these policies when deciding whether to enact them.